(untitled) (Tạp chí Nghiên cứu Khoa học Công đoàn, 2020)
Integration and globalization have been an inevitable trend in the development process of each nation, region and in the world. International labor division has been increasingly in depth and the rapid development of science and technology has accelerated the internationalization process of the world’s economy. This process is clearly demonstrated in the very rapid increase in international trade changes and financial services. Along with the formation of free trade zones and associated blocks in the world such as: the World Trade Organization (WTO), Asia-Pacific Economic Cooperation (APEC), ASEAN Economic Community (AEC), Trans-Pacific Partnership Agreement (TPP), ... the world is in the process of strong integration and globalization.